Cn‐AMP2 from green coconut water is an anionic anticancer peptide. (19th September 2014) - Prabhu, Saurabh; Dennison, Sarah R.; Mura, Manuela; Lea, Robert W.; Snape, Timothy J.; Harris, Frederick
<x xml:space="preserve">Abstract</x> Globally, death due to cancers is likely to rise to over 20 million by 2030, which has created an urgent need for novel approaches to anticancer therapies such as the development of host defence peptides. Cn‐AMP2 (TESYFVFSVGM), an anionic host defence peptide from green coconut water of the plant Cocos nucifera, showed anti‐proliferative activity against the 1321N1 and U87MG human glioma cell lines with IC50 values of 1.25 and 1.85 mM, respectively. The membrane interactive form of the peptide was found to be an extended conformation, which primarily included β‐type structures (levels > 45%) and random coil architecture (levels > 45%). On the basis of these and other data, it is suggested that the short anionic N‐terminal sequence (TES) of Cn‐AMP2 interacts with positively charged moieties in the cancer cell membrane. Concomitantly, the long hydrophobic C‐terminal sequence (YFVFSVGM) of the peptide penetrates the membrane core region, thereby driving the translocation of Cn‐AMP2 across the cancer cell membrane to attack intracellular targets and induce anti‐proliferative mechanisms. This work is the first to demonstrate that anionic host defence peptides have activity against human glioblastoma, which potentially provides an untapped source of lead compounds for development as novel agents in the treatment of these and other cancers. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.